Impacts of salinity and fish-exuded kairomone on the survival and macromolecular profile of Daphnia pulex - Bezirci, Gizem (Ecotoxicology (London, England), 2012)
Global warming is already causing salinization of freshwater ecosystems located in semi-arid regions, including Turkey. Daphnids, which are important grazers on phytoplankton and a major food source for fish and invertebrates, are sensitive to not only changes in salinity levels, but also presence of predators. In this study, the interactive effect of salinity toxicity (abiotic factor) with predation pressure mimicked by the fish-exuded kairomone (biotic factor) and the effect of salt acclimation on daphnids were investigated. Impacts of these stressors on daphnid survival, life history and molecular profile were observed. The presence of the kairomone antagonistically alters the effect of salinity, as observed from the 24- and 48-h LC(50) values and survival results. Molecular findings provided solid evidence to this antagonism at even lower salt concentrations, for which antagonism was not evident with organismal data. Fish predation counterbalances the negative effect of salinity in terms of reserve energy density. Therefore, it is important to investigate multiple stressor effects in ecotoxicological bioassays complemented with molecular techniques. The single effect of increasing salinity resulted in increased mortality, decreased fecundity, and slower somatic growth in Daphnia, despite their acclimation to salinity. This insignificance of acclimation indicates that Daphnia do not have any physiological mechanisms to buffer the adverse effects of salinity, making it a very crucial factor. Salinity-induced reduction in population growth rate of freshwater keystone species Daphnia-despite acclimation-indicates that global warming-induced salinity may cascade through the food web and lead to dramatic environmental consequences in the structure of lake ecosystems